Dialect Variations the Enrichment of Standard Igbo Language: A Linguistic Study - Dom-Anyanwu Ngozi Lovina; Benjamin F.C Nwokedi; Eneremadu Queen Esther Chioma (MultiTech Publisher, 2023)
Historically, many languages of the world evolved their standard forms through centralized control or political unity. Considering the decentralized natured of the Igbo unity, the dream evolving a standard form through much means, remains a mirage and unrealistic. Therefore, Igbo scholars are forced with the task of achieved this goal, we must used what we have to get what we want. In other words, we cannot enrich the evolving standard Igbo by using the dialectal variants in the language. Igbo dialectal variation and the dialect variants as synonyms, with comparative study of five dialects: Owerri, oguuta, Afikpo, Nnewi and Ngwa (ibeme) at the phonological, morphological and syntactic levels. The paper discuss the standard Igbo vis-a- vis dialects and meta-language as the tool for its enrichment which consist of the effect of dialectal variation, including the conclusion and recommendations made that rather than being a conclusive linguistic study on dialectal variation for the enrichment of standard Igbo, would serve as a stimulus for further intensive researches.